2017
DOI: 10.1155/2017/3834827
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Commuting Injuries in Spain and Their Impact on Injury Prevention

Abstract: A gender analysis of workers injured while commuting in Spain is presented, distinguishing between injury due to traffic-related accidents and injury due to other causes. Method. A total of 266,646 traffic-related injuries and 168,129 nontraffic-related injuries are studied over the period 2006–2010. Results. In Spain, the accident rate recorded in working hours is much higher among men; nevertheless, it is curious that commuting-related accident rates are higher among women than men, in both traffic-related i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…This phenomenon gets worse when there is a lack of sleep and can have effects up to 4 hours after awakening [ 36 ]. Sleep inertia would be consistent with the fact that commuting accidents occur largely in the morning rather than in the afternoon [ 5 , 10 ]. Simulated driving studies have found that sleep inertia impairs the performance of sleep-deprived drivers [ 37 ], mainly when they drive in the morning rather than in the afternoon [ 14 ].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This phenomenon gets worse when there is a lack of sleep and can have effects up to 4 hours after awakening [ 36 ]. Sleep inertia would be consistent with the fact that commuting accidents occur largely in the morning rather than in the afternoon [ 5 , 10 ]. Simulated driving studies have found that sleep inertia impairs the performance of sleep-deprived drivers [ 37 ], mainly when they drive in the morning rather than in the afternoon [ 14 ].…”
Section: Discussionmentioning
confidence: 76%
“…While workplace accidents decrease yearly, commuting accidents increase [ 2 – 4 ]. By sex, more men are involved in workplace accidents while women in commuting accidents [ 2 , 5 ]. Global data indicate that commuting accidents have more severe consequences of death and permanent disability than workplace accidents and imply higher economic costs [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon gets worse when there is a lack of sleep and can have effects up to four hours after awakening [36]. Sleep inertia would be consistent with the fact that commuting accidents occur largely in the morning rather than in the afternoon [5] [10]. Simulated driving studies have found that sleep inertia impairs the performance of sleepdeprived drivers [37], mainly when they drive in the morning rather than in the afternoon [14].…”
Section: Discussionmentioning
confidence: 77%
“…While workplace accidents decrease yearly, commuting accidents increase [2] [3] [4]. By sex, more men are involved in workplace accidents while women in commuting accidents [2] [5]. Global data indicate that commuting accidents have more severe consequences of death and permanent disability than workplace accidents and imply higher economic costs [6].…”
Section: Introductionmentioning
confidence: 99%
“…While drivers do choose to delay or forgo driving in poor weather conditions [ 1 , 2 ], reduced driving is less apparent during the peak driving hours of 6:00 to 9:00 a.m., the common time period for the daily commute to work [ 1 ]. The commute to work is a significant source of employee injury, with motor vehicle crashes occurring most frequently during the morning and evening hours [ 3 , 4 ]. Although injury during a commute to work is not considered a work-related injury in the United States (OSHA 29 CFR 1904.5(b)(2)), the National Institute for Occupational Safety and Health (NIOSH) has expanded current injury and illness prevention efforts to non-occupational sources of increased risk in order to promote overall worker wellbeing through the concept of Total Worker Health ® (TWH) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%